The Motor Skills of Adolescents with Hearing Impairment in Regular Physical Education Environment - Tan, S.; Nonis, Karen (International Journal of Special Education, 2017)
Studies have reported that, with the exception of balance, children and adolescents with and without hearing impairment (HI) could have similar motor skills proficiency. However, motor proficiency traits in this age group have not been defined in inclusive Physical Education (PE) settings. This study compared the gross and fine motor skills of twenty four female adolescents with and without HI (HI group: n = 7; Hearing group: n = 17; age range: 13 – 16 years) in a regular school in Singapore. The McCarron Assessment of Neuromuscular Development (MAND; McCarron, 1997) was used in this study. The HI group performed significantly poorer in terms of kinaesthetic integration (KI) than the Hearing group (p = .05). However, a non-significant difference was found in overall gross and fine motor skills (p > .05). The findings of this study imply poorer balance abilities of adolescents with HI when compared to their peers with typical hearing. Therefore, structured physical activities with a focus on balance development are proposed to improve the balance proficiency of adolescents with HI.